Comparing the efficacy of visual inspection with acetic acid and lugol’s iodine as a screening tool for detecting cervical lesions in asymptomatic women of reproductive age group with colposcopy and biopsy in a tertiary care hospital - Marimuthu, Kavitha; Loganathan, Malarvizhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: A quarter of global burden of carcinoma cervix is experienced in India, where about 1, 26,000 new cases and 71,000 deaths attribute to cervical cancer are estimated to occur each year. Cervical cancer constitutes 15-55% of all female cancer and value of age standardized incidence ranges from 17.2 to 55 per 1 lakh women in different region in India with 5-year survival rate of less than 40% as most are detected at advanced stage. The objective of present study was to identify the incidence of cervical lesions in sexually active asymptomatic women. Methods: This prospective study conducted in a tertiary care hospital for 1 year. This study comprises study subject of 734 women who were attending general and gynecology OPD. All 734 patients were subjected to visual inspection and magnification (VIA/VILI), colposcopy and biopsy was done in the positive patients. Results: Of 734 cases studied, colposcopy was positive in 97 (13.1%). Among 97 cases who were colposcopy positive, VIA/VILI was positive in 90 cases. Colposcopy guided biopsy was positive in 97 cases. The sensitivity of VIA/VILI in detecting preinvasive lesions was 91.84% and specificity was 100% when compared with colposcopy which has sensitivity 98.98% and specificity 100%. Conclusions: There is an enormous increase in the incidence of cancer cervix in geometric proportion. This can be controlled only with the introduction of mass screening programme by magnavision in a coordinated way in low resource settings.